Silo Guard II® for alfalfa, corn, and forage sorghum silages - K. Bolsen; H. Ilg; M. Hinds (Kansas Agricultural Experiment Station Research Reports, 1984)
In the first trial, calves fed Silo Guard II®-treated forage sorghum silage were 4.2% more efficient than those fed the control silage. Silo Guard II reduced the amount of heat produced during the ensiling process, and increased the dry matter recovered from the silo by nearly 7 percentage units (84.1 vs. 77.2%). The more efficient gain and reduced shrink loss for the treated silage gave 8.3% extra pounds of calf gain per ton of crop ensiled when compared with the control silage. In the second trial, laboratory silos were used to evaluate three levels of Silo Guard II (.5, 1.0, and 2.0 lb per ton), with each of the following crops: direct-cut alfalfa, wilted alfalfa, corn and forage sorghum. All levels of Silo Guard II improved dry matter recoveries and treated silages underwent more efficient fermentations. Adding Silo Guard II at .5 lb was not as effective as the higher application rates.
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Alfalfa; Corn; Sorghum; Silage